Ventilator associated pneumonia caused by extensive-drug resistant Acinetobacter species: Colistin is the remaining choice - Ahmed Hasanin; Ahmed Mukhtar; Akram El-adawy; Hossam Elazizi; Ahmed Lotfy; Heba Nassar; Doaa Ghaith (Egyptian Journal of Anaesthesia, 2016)
Introduction: Ventilator-associated pneumonia [VAP] is associated with increased morbidity and mortality especially when caused by extensive drug resistant [XDR] pathogens. Till now, little is known regarding the exact pathogenesis of XDR Acinetobacter baumannii [XDR-AB] infection. The aim of the present study was to identify prevalence and risk factors for VAP caused by XDR-AB in our intensive care unit, and to test the susceptibility pattern of tigecycline, carbapenems, and Colistin among the isolates. Methods: A prospective cohort study was conducted to enroll patients who developed VAP over 18-month period. All possible risk factors were documented as well as patient outcome. Susceptibility testing for the isolates was performed using inhibitory concentrations [MICs] determined by Epsilometer tests (E-tests) to Carbapenems, Tigecycline, and Colistin. Results: Among 544 consecutive patients admitted to our ICU during 18 months, Forty-seven patients developed VAP. The prevalence of XDR-AB was 63.8% (30 patients). No specific factor was associated with increase of the risk of acquisition of AB-VAP in our cohort either by univariate or by multivariate analysis. Carbapenems showed poor activity against all isolates [MIC range 10–128 mg/L]. Tigecycline showed good activity against only 15 isolates [MIC range 0.25–2 mg/L]. Colistin demonstrated potent in vitro activity against all isolates of AB [MIC range 0.016–1 mg/L]. Conclusions: XDR AB-VAP is endemic in our ICU without a definite factor associated with increased risk of infection. Given that almost half of the strains are also resistant to tigecycline, colistin appears to be an appropriate first-line antimicrobial drug in critically ill patients developing VAP based on invitro results.